1989
DOI: 10.3354/dao006131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental pollutants on the chemiluminescence of hemocytes from the American oyster Crassostrea virginica

Abstract: An assay measuring the chemiluminescent response of hemocytes from the oyster Crassostea virginica was used to assess the effects of environmental pollutants on phagocytosis. In vivo and in vitro effects of heavy metals (copper, cadmium, zinc, and aluminum), pesticides (dieldrin and chlordane), and organic compounds (naphthalene and 2,4-dinitrophenol) on the chemiluminescent response of stimulated oyster hemocytes were tested. In most cases, exposure to a hlgh pollutant concentration resulted in a decreased ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 6 publications
3
40
1
Order By: Relevance
“…Correlation between hydrocarbon concentrations and immune parameters: *p < 0.05; **p < 0.01. THC, total hydrocarbon concentration; PAH, polycyclic aromatic hydrocarbon A study using the chemiluminescence assay tested a variety of compounds (including naphthalene) on Crassostrea virginica haemocytes and found generally that high contaminant concentrations depressed the response (Larsson et al 1989). Pipe et al (1995b) used the NBT assay on the haemocytes of mussels from the Venice lagoon and found that intra-cellular superoxide appeared greater during periods of lower organic contaminant concentrations (principally PCBs; PAHs were not measured).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between hydrocarbon concentrations and immune parameters: *p < 0.05; **p < 0.01. THC, total hydrocarbon concentration; PAH, polycyclic aromatic hydrocarbon A study using the chemiluminescence assay tested a variety of compounds (including naphthalene) on Crassostrea virginica haemocytes and found generally that high contaminant concentrations depressed the response (Larsson et al 1989). Pipe et al (1995b) used the NBT assay on the haemocytes of mussels from the Venice lagoon and found that intra-cellular superoxide appeared greater during periods of lower organic contaminant concentrations (principally PCBs; PAHs were not measured).…”
Section: Discussionmentioning
confidence: 99%
“…Chlordan, an insecticide, demonstrated effects on C. virginica hemocyte phagocytosis at 250 碌M in vitro (Larson et al, 1989). A decreased phagocytosis activity was observed after a triforine exposure in the eastern oyster, C. virginica (Alvarez and Friedl, 1992).…”
Section: Immunotoxicity In Marine Bivalves and Susceptibilty To Infecmentioning
confidence: 99%
“…Pentachlorophenol decreased the production of ROS by the inhibition of NADPH production in the eastern oyster, Crassostrea virginica (Baier- . Dieldrin, tested in vitro on C. virginica hemocytes induced a decrease of chemiluminescence at concentrations ranging from 3 to 300 碌M (Larson et al, 1989). Hemocytes of C. virginica exposed to chlorothalonil (fungicide) for 20 h at concentrations between 4 nM and 2 碌M showed no modification of cell mortality and phagocytosis, but a decrease of ROS production (Baier- Anderson & Anderson, 2000).…”
Section: Immunotoxicity In Marine Bivalves and Susceptibilty To Infecmentioning
confidence: 99%
“…For example, many investigations have evaluated the release of metals into aquatic systems because of the high threat to human health (Larson et al 1989;Fisher et al 2000;Fournier et al 2001;Matozzo et al 2001;Oliver et al 2001Oliver et al , 2003Gagnaire et al 2004;Parry and Pipe 2004). Although organic pollutants have received less attention, polycyclic aromatic hydrocarbons (PAHs), which are constituents of crude oil, have been reported to alter hemocyte function in marine bivalves.…”
Section: Introductionmentioning
confidence: 99%